Comparative Study on Life of High-speed Bearings at Ultimate Low Temperature - Zhao, Weihua; Chen, Qinghou; Ma, Cong; Yang, Danfeng; Yang, Kenan; Hu, Lai (Manufacturing Technology Journal, 2021)
Aiming to improve the working life of high-speed rail bearings, this paper puts forward a comparative study on different types of high-speed rail bearings at extreme low temperature. The model of bearing life is established. In the whole test process, it is found that the change trends of bearing temperature, environment temperature and torque are basically the same. In the equilibrium temperature relationship between SKF and ZH bearings, the temperature divergence of SKF bearings finally appears. In the ZH bearings, bearing 4 appears irregular sharp drop at the end. However, the temperature changes of the two brands of bearings are between-150 extcelcius and -170 extcelcius. And the friction coefficient is proportional to the ratio of torque. In the comparison of grinding amount, the wear amount of ZH bearings is far lower than that of SKF bearings, with a difference of about 0.5 mm. This shows that the production process and surface treatment methods of the two types bearing are completely different.
Keywords: High-speed rail bearing; Life span; Temperature; Wear; Torque